THE EVOLUTION OF INTELLIGENCE MODELS: FROM PSYCHOMETRIC THEORIES TO SYSTEMIC-FUNCTIONAL APPROACHES AND THEIR IMPLICATIONS FOR SPECIAL PEDAGOGY - Markova Olesya Anatolyevna (Web of Journals Publishing, 2025)
This paper presents a comprehensive theoretical analysis of the evolution of scientific models of intelligence, tracing the paradigmatic shift from classical psychometric theories to modern systemic-functional concepts. It examines the foundational models of Spearman (g-factor), Cattell (Gf-Gc theory), and Guilford (SOI model), contrasting them with the contemporary approaches of Sternberg (Triarchic Theory) and Gardner (Theory of Multiple Intelligences). The central argument is that this evolution from a static, deficit-focused view to a dynamic, resource-oriented perspective has profound implications for special pedagogy. The paper highlights how modern models provide a framework for qualitative assessment and individualized intervention, shifting the focus from measuring deficits to identifying and leveraging the unique cognitive strengths of children with special educational needs. The analysis underscores the necessity of developing new diagnostic tools that align with these contemporary, multidimensional views of intelligence to improve psycho-pedagogical support.
Keywords: Intelligence models, special pedagogy, psychometric theory, g-factor, fluid and crystallized intelligence, triarchic theory of intelligence, multiple intelligences, cognitive assessment, special educational needs (SEN).